OsbHLH067, OsbHLH068, and OsbHLH069 redundantly regulate inflorescence axillary meristem formation in rice. - Tingting Xu; Debao Fu; Xiaohu Xiong; Junkai Zhu; Zhiyun Feng; Xiaobin Liu; Changyin Wu (PLoS Genetics)
Rice axillary meristems (AMs) are essential to the formation of tillers and panicle branches in rice, and therefore play a determining role in rice yield. However, the regulation of inflorescence AM development in rice remains elusive. In this study, we identified no spikelet 1-Dominant (nsp1-D), a sparse spikelet mutant, with obvious reduction of panicle branches and spikelets. Inflorescence AM deficiency in nsp1-D could be ascribed to the overexpression of OsbHLH069. OsbHLH069 functions redundantly with OsbHLH067 and OsbHLH068 in panicle AM formation. The Osbhlh067 Osbhlh068 Osbhlh069 triple mutant had smaller panicles and fewer branches and spikelets. OsbHLH067, OsbHLH068, and OsbHLH069 were preferentially expressed in the developing inflorescence AMs and their proteins could physically interact with LAX1. Both nsp1-D and lax1 showed sparse panicles. Transcriptomic data indicated that OsbHLH067/068/069 may be involved in the metabolic pathway during panicle AM formation. Quantitative RT-PCR results demonstrated that the expression of genes involved in meristem development and starch/sucrose metabolism was down-regulated in the triple mutant. Collectively, our study demonstrates that OsbHLH067, OsbHLH068, and OsbHLH069 have redundant functions in regulating the formation of inflorescence AMs during panicle development in rice.